The Effects of International Scrutiny on Manufacturing Workers: Evidence from the Rana Plaza Collapse in Bangladesh - Laurent Bossavie; Yoon Y. Cho; Rachel Heath (Institute of Labor Economics (IZA), 2020)
After the tragic factory collapse of Rana Plaza in 2013, both the direct reforms and indirect responses of retailers have plausibly affected workers in the Ready Made Garment (RMG) sector in Bangladesh. These responses included a minimum wage increase, high profile but voluntary audits, and an increased reluctance to subcontract to smaller factories. This paper uses six rounds of the Labor Force Survey and adopts a synthetic control approach to evaluate the net effects of these changes on garment workers. While we find that working conditions did improve, we find evidence of adverse effects on several other outcomes for workers. In particular, while the reforms initially increased female workers' wages, their wages had fallen an estimated 20 percent three years after Rana Plaza. We also show suggestive evidence that female workers' contracts displayed a similar short-term increase and ultimate long-term decrease. Male workers, by contrast, if anything experienced only short-term adverse effects.
Keywords: F16; J16; J31; J32; J81; O12; 330; garment sector; working conditions; gender; minimum wage